Mechanisms of action and clinical use of specific reversal agents for non-vitamin K antagonist oral anticoagulants. (4th May 2018) - Andresen, Kristoffer; Atar, Dan; Gjertsen, Erik; Ghanima, Waleed; Roseth, Svein; Johansen, Odd Erik
Abstract: Objectives. With a steadily growing number of patients with non-valvular atrial fibrillation, anticoagulation use increases. Anticoagulation therapy is associated with increased risk of serious bleeding and an increased complexity in management of patients in need for urgent surgery. We wanted to assess the magnitude of this challenge as well as review current and potential future clinical management strategies. Design. A review of the literature on the magnitude of patients using antigoaculants in potential need for acute restoration of hemostasis was conducted, as well as current status of reversal agents for non-vitamin K antagonist oral anticoagulants (NOACs). Additionally, a case illustration of its use is presented. Results. Two main groups of patients may need acute restoration of hemostasis, those in need of acute surgery or acute invasive procedures, ∼ 2% of patients annually, and those with serious and critical hemorrhage, ∼1.5% annually. One specific reversal agent is available on the market (idarucizumab) and two (andexanet alfa, ciraparantag) are in clinical development. Idarucizumab is a specific antidote for the thrombin inhibitor dabigatran while andexanet alfa is factor Xa inhibitor class-specific currently in late-stage development. Ciraparantag is a universal reversal agent in early-phase development. These agents can facilitate effective management of bleeding or bleeding risk, as illustrated in a patient on dabigatran in urgent need for a pacemaker. Conclusions. Amongst patients using anticoagulants, around 3.5%, could be in need of immediate restoration of hemostasis annually. The availability and use of specific reversal agents for NOACs could be crucial for the clinical outcomes.